Antibacterial Potential of Lactobacillus-Derived Bacteriocin-Like Inhibitory Substances (BLIS) Against Group B Streptococcus (GBS): A Biotherapeutic Approach - Brown, Samuel Tamunoiyowuna Cockeye; Mohammed, Ikrimah Usman; Onyemaechi, Eze Emmanuel (African Journal of Clinical Medicine and Pharmacy Research, 2025)
Background: Lactic acid bacteria (LAB) are a diverse group of Gram-positive, non-spore-forming bacteria known for their ability to produce antimicrobial substances such as bacteriocins and bacteriocin-like inhibitory substances (BLIS). Aim: This study aimed to isolate, characterize, and evaluate the antimicrobial activity of BLIS produced by LAB against Group B Streptococcus (GBS) from vaginal samples of pregnant women attending Federal University Teaching Hospital Wukari, Nigeria. Methods: Vaginal swabs were collected from 50 pregnant women and processed for the isolation of LAB and GBS using selective media and biochemical characterization. Bacteriocin-like inhibitory substances were extracted from LAB isolates and tested against GBS using the disk diffusion method. The effects of temperature and pH on BLIS activity were also evaluated. Results: The results revealed that LAB isolates exhibited varying degrees of antimicrobial activity against GBS. The BLIS produced were found to be moderately heat-stable, retaining activity up to 90°C but showing loss at 100°C. BLIS produced by selected isolates (S8, S4, and S2) maintained antimicrobial activity across a broad temperature range (30°C –100°C) and different pH conditions (5.5–8.0). The inhibitory effects of BLIS remained stable across different pH levels, reinforcing their potential as alternative antimicrobial agents. There was no significant difference in activity between crude and partially purified BLIS, suggesting they may be low-molecular-weight peptides. Antibiotic susceptibility testing showed that GBS isolates were resistant to levofloxacin, amoxicillin, and ampiclox, while ciprofloxacin, erythromycin, chloramphenicol, and streptomycin remained effective. Conclusion: This study underscores the potential of LAB-derived BLIS as natural antimicrobial agents for managing GBS infections. The effectiveness and stability of Lactobacillus-derived BLIS in various environmental conditions suggest its suitability for pharmaceutical and food industry applications. Further research on purification and molecular characterization could enhance its use in antimicrobial therapy.